Preliminary investigation on a new natural based poly(gamma‐glutamic acid)/Chitosan bioink. Issue 7 (11th March 2020) - Pisani, Silvia; Dorati, Rossella; Scocozza, Franca; Mariotti, Camilla; Chiesa, Enrica; Bruni, Giovanna; Genta, Ida; Auricchio, Ferdinando; Conti, Michele; Conti, Bice
Abstract: The study aims to investigate a novel bioink made from Chitosan (Cs)/ poly(gamma‐glutamic acid) (Gamma‐PGA) hydrogel that takes advantage of the two biodegradable and biocompatible polymers meeting most of the requirements for biomedical applications. The bioink could be an alternative to other materials commonly used in 3D‐bioprinting such as gelatin or alginate. Cs/ Gamma‐PGA hydrogel was prepared by double extrusion of Gamma‐PGA and Cs solutions, where 2 × 10 5 human adult fibroblasts per ml Cs solution had been loaded, through Cellink 3D‐Bioprinter at 37°C. A computer aided design model was used to get 3D‐bioprinting of a four layers grid hydrogel construct with 70% infill. Hydrogel characterization involved rheology, FTIR analysis, stability study (mass loss [ML], fluid uptake [FU]), and cell retaining ability into hydrogel. 3D‐bioprinted hydrogel gelation time resulted to be <60 s, hydrogel structure was maintained up to 36.79 Pa shear stress, FTIR analysis demonstrated Gamma‐PGA/Cs interpolyelectrolyte complex formation. The 3D‐bioprinted hydrogel was stable for 35 days (35% ML) in cell culture medium, with increasing FU. Cell loaded 3D‐bioprinted Cs 6% hydrogel was able to retain 70% of cells which survived to printing process and cell viability was maintained during 14 days incubation.